(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Communicative method is occurrence in demand in up-to-date terms of education, where educational process is the model of communication. Specialty language is regarded in communicative aspect on the texts of sublanguage in this article. Individual approach for the development of communicative skills is offered.